Confidence Level of Bantul Archery Athletes in Facing the 2022 Yogyakarta Special Region Porda XVI Event - Zaki Mubarok; Ardhika Falaahudin; Dody Tri Iwandana (Journal Physical Health Recreation (JPHR), 2022)
This study aims to determine the Level of Confidence of Bantul Archery Athletes in Facing the PORDA XVI DIY Event in 2022, Special Region of Yogyakarta. The data analysis used in this research is quantitative descriptive statistical analysis. Descriptive statistics are statistics used to analyze data by describing or describing the data that has been collected as it is without the intention of making generally accepted conclusions or generalizations. The results of this study indicate the level of confidence in Bantul archery athletes in facing the PORDA XVI DIY event in 2022, Yogyakarta Special Region from internal factors, external factors and a combination of these two factors.